Transient Stability Improvement using SSSC and STATCOM - et. al, R.Naveena Bhargavi (International Journal of Advanced Science and Technology, 2020)
Nowadays, due to the rapid growth in the power demand and with the increasing complexity of power system network, may lead to overloading and loss of synchronism of the power system network. Hence Transient stability is of much concern and put new challenges to power system engineers in terms of Power system stability and security during major disturbances. Hence, FACTS technology has become popular to meet these challenges. FACTS devices make use of power electronic converters to enhance the power transmission capability and thereby improves the system stability. This paper compares the performance of SSSC with STATCOM. The work is carried out in the MATLAB/SIMULINK environment.